Analysis of The Influence of Lack of Cellular Network on The Quality of Education in Schools in Long Gelawang Village - Jemeq, Margareta; Rangan, Andi Yusika; Khair, Ahmad Abul (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2025)
Cellular networks are one of the supporting factors in implementing learning activities, especially in the digital era which requires connectivity to access information and online learning technology. However, not all areas in Indonesia have adequate network infrastructure, including Long Gelawang Village. This study aims to analyze the impact of limited cellular networks on the quality of education in the area. The quantitative approach was used with descriptive statistical methods and Spearman correlation tests. Data were obtained from 55 respondents consisting of students and teachers through questionnaires and interviews. The results of the normality test showed that the data were not normally distributed, so non-parametric analysis was used. The results showed that the relationship between network limitations and education quality was very weak (ρ = 0.143) and not significant (p = 0.299). This means that network limitations do not directly impact the quality of education. Local efforts such as the use of printed teaching materials, hands-on learning, and parental and community involvement help maintain the continuity of education. These findings emphasize that improving the quality of education in remote areas depends not only on technology, but also on a collaborative and locally based approach.